If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(x+3)=-8x-36
We move all terms to the left:
-6(x+3)-(-8x-36)=0
We multiply parentheses
-6x-(-8x-36)-18=0
We get rid of parentheses
-6x+8x+36-18=0
We add all the numbers together, and all the variables
2x+18=0
We move all terms containing x to the left, all other terms to the right
2x=-18
x=-18/2
x=-9
| 3^5x=9^2 | | (3x−9)+(x+3)=180 | | 7x+9=5+15 | | 996(12+69)=12x+77 | | -22/3x=-4/7 | | a/a-7=32 | | x/1.4=1.4 | | 27x+153=180 | | 22/3-x=-4/7 | | 15x-10/5=-2 | | 69=8x+21 | | 64y^+7=32 | | 12w=3w | | n/n-1=87 | | -6x-11=-x-14 | | 4x+1/3+2x+1/3=3x-7/5+6 | | 48+9w=15w | | -5/3x+1=2/2x-3 | | x•3x+5x=180 | | -8x+3-5x=7+2(x-7) | | 3z+2/9=4z+1/9 | | (7x)+40=20 | | (7x)+40=22 | | 4(-6n-4)=128 | | 2/9(3x-1/2)=1/5x+1/3 | | r^-16=-7 | | -10=-5x-25*4 | | x/14+30=70 | | 16p+1=-31 | | 2(s+11)=5(s+2)* | | 2/5x-81/8-3/4(14/15x-55/9)=27/10x-25/6+3/4(x+51/6) | | 8(g-3)=24* |